Effects of fermented black ginseng on wound healing mediated by angiogenesis through the mitogen-activated protein kinase pathway in human umbilical vein endothelial cells - Park, Jun Yeon; Lee, Dong-Soo; Kim, Chang-Eop; Shin, Myoung-Sook; Seo, Chang-Seob; Shin, Hyeun-Kyoo; Hwang, Gwi Seo; An, Jun Min; Kim, Su-Nam; Kang, Ki Sung (KOREAN SOC GINSENG, 2018)
Background: Fermented black ginseng (FBG) is produced through several cycles of steam treatment of raw ginseng, at which point its color turns black. During this process, the original ginsenoside components of raw ginseng (e.g., Re, Rg1, Rb1, Rc, and Rb2) are altered, and less-polar ginsenosides are generated (e.g., Rg3, Rg5, Rk1, and Rh4). The aim of this study was to determine the effect of FBG on wound healing. Methods: The effects of FBG on tube formation and on scratch wound healing were measured using human umbilical vein endothelial cells (HUVECs) and HaCaT cells, respectively. Protein phosphorylation of mitogen-activated protein kinase was evaluated via Western blotting. Finally, the wound-healing effects of FBG were assessed using an experimental cutaneous wounds model in mice. Results and Conclusion: The results showed that FBG enhanced the tube formation in HUVECs and migration in HaCaT cells. Western blot analysis revealed that FBG stimulated the phosphorylation of p38 and extracellular signal-regulated kinase in HaCaT cells. Moreover, mice treated with 25 mg/mL of FBG exhibited faster wound closure than the control mice did in the experimental cutaneous wounds model in mice. (C) 2017 The Korean Society of Ginseng, Published by Elsevier Korea LLC.
Keywords: FIBROBLAST-GROWTH-FACTOR; VASCULAR-PERMEABILITY FACTOR; IN-VITRO; PANAX-GINSENG; EXTRACELLULAR-MATRIX; PROLIFERATION; INFLAMMATION; MODULATION; MECHANISMS; MIGRATION